2017
DOI: 10.1002/ptr.5905
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids Lower Plasma Leptin Concentrations: A Meta‐analysis

Abstract: Curcumin is a naturally occurring polyphenol that has been suggested to improve several metabolic diseases. Leptin is an adipokine involved in metabolic status and appetite, with marked crosstalk with other systems. Available data suggest that curcumin may affect leptin levels; therefore, this meta-analysis was performed to evaluate this. A systematic review and meta-analysis were undertaken on all randomized controlled trials of curcumin studies that included the measurement of leptin. The search included Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…On the basis of the results of these studies, it was found that curcumin consumption exerted a positive effect on weight management of obese individuals, lowering blood lipids and improving glycemic control. This result is in line with a recent meta‐analysis, which showed that curcumin supplementation can lower plasma leptin levels (Atkin, Katsiki, Derosa, Maffioli, & Sahebkar, ), and a systematic review that documented a decrease in fasting glucose levels after 2 hr of oral glucose tolerance test, glycosylated hemoglobin levels A1c, and insulin resistance (HOMA‐IR; Demmers, Korthout, van Etten‐Jamaludin, Kortekaas, & Maaskant, ). Moreover, curcumin administration in patients suffering from various types of cancer, such as prostate, breast, pancreatic, biliary tract, and colon cancer may improve overall health, ameliorating the adverse side effects induced by common pharmaceutical regimens and, in some cases, slowing down disease progression.…”
Section: Discussionsupporting
confidence: 86%
“…On the basis of the results of these studies, it was found that curcumin consumption exerted a positive effect on weight management of obese individuals, lowering blood lipids and improving glycemic control. This result is in line with a recent meta‐analysis, which showed that curcumin supplementation can lower plasma leptin levels (Atkin, Katsiki, Derosa, Maffioli, & Sahebkar, ), and a systematic review that documented a decrease in fasting glucose levels after 2 hr of oral glucose tolerance test, glycosylated hemoglobin levels A1c, and insulin resistance (HOMA‐IR; Demmers, Korthout, van Etten‐Jamaludin, Kortekaas, & Maaskant, ). Moreover, curcumin administration in patients suffering from various types of cancer, such as prostate, breast, pancreatic, biliary tract, and colon cancer may improve overall health, ameliorating the adverse side effects induced by common pharmaceutical regimens and, in some cases, slowing down disease progression.…”
Section: Discussionsupporting
confidence: 86%
“…Curcumin, which represents by alone a constituent (up to ∼5%) of the traditional olistic medicine, is known as turmeric (Nakmareong et al, ; Nelson et al, ). Curcumin exerts a number of pharmacological actions of potential therapeutic interest (Atkin, Katsiki, Derosa, Maffioli, & Sahebkar, ; Kocaadam & Şanlier, ; Mantzorou, Pavlidou, Vasios, Tsagalioti, & Giaginis, ; Milani, Basirnejad, Shahbazi, & Bolhassani, ; Shen, Jiang, Yang, Wang, & Zhu, ; Soleimani, Sahebkar, & Hosseinzadeh, ), and it is extensively marketed worldwide as a nutraceutical (Santini & Novellino, ). Starting from the first clinical trial published in The Lancet in 1937 (Oppenheimer, ), more than 1,200 clinical trials involving more than 6,000 subjects have been carried out, and many systematic reviews have been published (Kunnumakkara et al, ).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Curcumin is a phyto‐polyphenolic pigment extracted from turmeric ( Curcuma longa ) . It has been widely used for therapeutic purpose histologically due to the intrinsic anti‐inflammatory, antioxidant and antitumour properties . The extensive investigations and exploitations have characterized the wide‐spectrum anticancer activity of curcumin against variety of human tumours including ovarian, breast, colon and so forth .…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] It has been widely used for therapeutic purpose histologically due to the intrinsic anti-inflammatory, [11,12] antioxidant [13] and antitumour properties. [14][15][16][17][18][19] The extensive investigations and exploitations have characterized the wide-spectrum anticancer activity of curcumin against variety of human tumours including ovarian, breast, colon and so forth. [20][21][22][23][24][25] The various modes of action have been proposed underlying its therapeutic function in treatment of human cancer, including inhibition of proliferation, induction of cell apoptosis and suppression of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%